Hypertrophic cardiomyopathy: current understanding and treatment objectives. Issue 3 (17th October 2008) - Soor, G S; Luk, A; Ahn, E; Abraham, J R; Woo, A; Ralph-Edwards, A; Butany, J
Abstract : The understanding of hypertrophic cardiomyopathy (HCM) has changed dramatically over the last few decades, and it is now understood to be caused by a mutation in one of several cardiac sarcomeric genes. Due to complications such as outflow tract obstruction, diastolic dysfunction, arrhythmias, stroke, infective endocarditis and sudden cardiac death, appropriate and early identification of these patients is imperative. This review attempts to summarise the current state of knowledge on HCM, and provide insight of the appropriate investigations needed in patients with HCM. It also outlines treatment strategies for these patients. Much remains unknown about this complex and intriguing disease, and continued research in identifying the genetic basis of HCM, along with the assessment of therapeutic strategies, will help to optimise patient care.